KETERKAITAN STRUKTUR KEPEMILIKAN, STRUKTUR MODAL DAN NILAI PERUSAHAAN - Herry Subagyo (Universitas Sains dan Teknologi Komputer, 2021)
This research aims to test the relation between ownership structures and capital structure firm value of basic industry & chemistry firm. This research places the capital structure as a mediating variable for the relationship between ownership structure and firm value. The sample used is a company listed on the Indonesia Stock Exchange for the period 2014-2019, using a purposive sampling technique got 115 samples that meet the criteria. Data processing using the IBM SPSS 23 series program as an analysis tool. The result is that management's ownership has a negative effect on capital structure, and a positive effect on firm value, while institutional ownership has a positive effect on capital structure, and a negative effect on firm value. This study also found that capital structure is a mediating variable of the relationship between management ownership and firm value. Keywords: ownership structure, capital structure, firm value